The Sustainability Strategy Analysis of EON UK - Lee, Chih-Shan (2008)
The energy sector plays a key role in sustainable development. Not only does it drives economic and social progress but also impacts on the environment. EON UK is one of the major energy suppliers in the UK power industry, it is critical to establish a sustainable strategy for the organisational development in the long-run.